Faith bias or religious expression: the real religious diversity challenge?. Issue 1 (2nd January 2017) - King, James E.; Franke, George R.
Abstract: In light of mixed results surrounding religion's influence on work-related outcomes, we explore theoretical and design alternatives in an effort to better understand and explain outcomes surrounding religious diversity. We integrate theory on social norms into the religious diversity literature in an effort to explain previous mixed findings and negative reactions toward religious group identity members in a work context. Using an experimental design that allows for the distinct treatment of workplace religious expression and religious identity, our results suggest that negative reactions are exhibited toward both in-group religious identities (i.e., Christians) and out-group religious identities (i.e., Muslims) when individuals are described as engaging in workplace religious expression. We identify perceived inappropriateness of workplace religious expression as a significant mechanism through which negative reactions toward workplace religious expressions emerge. Theoretical and practical implications are discussed.